2014
DOI: 10.1118/1.4901260
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spot size on plan quality of spot scanning proton radiosurgery for peripheral brain lesions

Abstract: For treating peripheral brain lesions--where proton therapy would be expected to have the greatest depth-dose advantage over photon therapy--the lateral penumbra strongly impacts the SS plan quality relative to photon techniques: proton beamlet sigma at patient surface must be small (<7.1 mm for three-beam single-field optimized SS plans) in order to achieve comparable or smaller brain necrosis NTCP relative to photon radiosurgery techniques. Achieving such small in-air sigma values at low energy (<70 MeV) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 57 publications
0
50
0
Order By: Relevance
“…Previous studies have indicated better organ sparing due to reduced PBS spot size for specific patient cases [25,26]. Chanrion et al [27] explored the consequences of unexpected spot size fluctuations on the target coverage in PBS.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated better organ sparing due to reduced PBS spot size for specific patient cases [25,26]. Chanrion et al [27] explored the consequences of unexpected spot size fluctuations on the target coverage in PBS.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent studies on head and neck treatment and brain radiosurgery have demonstrated the benefit of further reduction in spot size in the sparing of normal tissues, e.g. salivary and parotid glands and normal brain [57, 58]. Thus, to achieve higher conformity, it is beneficial to generate beamlets of smaller σ, particularly for treatment sites with depths < 10–12 cm.…”
Section: Treatment Delivery Related Challenges and Potential Solutmentioning
confidence: 99%
“…However, lateral and distal target penumbra of noncollimated IMPT fields are not necessarily smaller than from double scattering delivery . Aside from optimization dependencies, the conformity and lateral penumbra of an IMPT system are proportional to the proton beamlet spot size . Hence, IMPT therapy system spot sizes have shown a continual developmental trend toward smaller since inception.…”
Section: Introductionmentioning
confidence: 99%